2012
DOI: 10.1007/s00228-012-1341-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of the TYMS 3G/3G genotype with poor response and GGH 354GG genotype with the bone marrow toxicity of the methotrexate in RA patients

Abstract: The 3 G/3 G genotype of the TYMS gene may indicate predisposition of poor response to MTX and GG genotype of GGH -354 T > G polymorphism may have high predictive value for myelosuppression in RA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 34 publications
5
30
0
3
Order By: Relevance
“…High GGH expression was shown to be associated with a higher risk of developing advanced toxicity to pemetrexed, a multi-targeted antifolate, in patients with advanced breast cancer (Llombart-Cussac et al 2007). Furthermore, several recently identified and characterized functionally significant genetic and epigenetic polymorphisms of GGH have been reported to predict response to and toxicity of antifolate-based treatment in patients with several cancers (Cheng et al 2004;Kim et al 2008;Koomdee et al 2012;Silva et al 2013;Smit et al 2012;Wang et al 2014) and inflammatory arthritis (Dervieux et al 2004;Hayashi et al 2009;Jekic et al 2013;Owen et al 2012;van der Straaten et al 2007;Yanagimachi et al 2011). Our data herein provide evidence that GGH modulation significantly influences expression and CpG DNA methylation of genes involved in important biological pathways that might account for the observed effects of GGH modulation on cancer risk, prognosis, and treatment response.…”
Section: Discussionsupporting
confidence: 54%
“…High GGH expression was shown to be associated with a higher risk of developing advanced toxicity to pemetrexed, a multi-targeted antifolate, in patients with advanced breast cancer (Llombart-Cussac et al 2007). Furthermore, several recently identified and characterized functionally significant genetic and epigenetic polymorphisms of GGH have been reported to predict response to and toxicity of antifolate-based treatment in patients with several cancers (Cheng et al 2004;Kim et al 2008;Koomdee et al 2012;Silva et al 2013;Smit et al 2012;Wang et al 2014) and inflammatory arthritis (Dervieux et al 2004;Hayashi et al 2009;Jekic et al 2013;Owen et al 2012;van der Straaten et al 2007;Yanagimachi et al 2011). Our data herein provide evidence that GGH modulation significantly influences expression and CpG DNA methylation of genes involved in important biological pathways that might account for the observed effects of GGH modulation on cancer risk, prognosis, and treatment response.…”
Section: Discussionsupporting
confidence: 54%
“…It has been observed that carriers of a double 28-bp tandem repeat in the TS promoter exhibit lower TS gene expression and activity than those with triple 28-bp repeats [35]. Several studies exploring potential influence of TS 5′UTR repeats on MTX toxicity and efficacy in RA patients found patients homozygous for TS 5′UTR 3R allele required higher MTX dose and had poor response to MTX as compared with those with at least one 2R [23,36,37]. When 2R/2R genotype was incorporated in toxicogenetic index together with several other folate cycle polymorphisms, significant correlation with toxicity to MTX was seen [25].…”
Section: Effect Of Snps In Folate Metabolism On Mtx Response Researchmentioning
confidence: 99%
“…El genotipo no TT de GGH T16 C (rs1800909) se asoció con mayor riesgo de disfunción hepática y el polimorfismo-354 T GGH-G se relacionó con mayor riesgo de mielosupresión 20,22 .…”
Section: Características Poblacionales Polimorfismos Y Genotiposunclassified
“…Los PMF en el gen que codifica esta enzima incluye repetición en tándem (dos o tres repeticiones de una unidad de 28 pb) en la región potenciadora en el 5'-UTR. Los pacientes homocigotos para la triple (3R) repetición de alelo de TYMS, presentan aumento en la expresión ARNm TYMS y mayor actividad enzimática en comparación con aquellos con el alelo 2R 22 .…”
unclassified